Scientific Reports on the Efficacy of Homeopathy in Cardiac Diseases in the Elderly – An Analysis of their Correlation with Materia Medica (Homoeopathy for All, 2023)
Ageing is a biological process that  cannot be reversed. Increasing  age in the later part of life also  makes a person more susceptible  to the extrinsic factors, thus raising  the health risks. These health  risks become a threat since they  encounter the organs undergoing  senile changes. The word senile  refers to the physical and mental  decline, which is associated with the  old age. The changes encountered  by the body during senility includes  problems like stiffening of blood  vessels and arteries, diminishing and  weakening of bones and muscles  reducing flexibility, affections of  stability and balance due to improper  coordination, constipation due to  changes in intestines, diminishing  vision or power of hearing, etc.  Amongst all, the problem of concern  is the cardiovascular diseases.
Keywords: Increasing; diminishing; diseases